Pemberdayaan Generasi Z melalui Edukasi Karier dan Kewirausahaan di Era Dgitial - Hamrullah, Dwi Evayanti; Febriati, Farida (Universitas Pahlawan Tuanku Tambusai, 2026)
Generation Z lives in a digital era characterized by rapid changes in the world of work, technological developments, and the emergence of digital-based entrepreneurial opportunities. These conditions require young people to have the ability to plan their careers adaptively while developing an entrepreneurial mindset from an early age. This article is a scientific reflection of an online educational activity themed “Career Planning for Gen Z” attended by undergraduate and graduate students and the general public. The purpose of this paper is to describe the material presented, analyze participant responses, and formulate practical strategies for Generation Z in preparing for their future careers. The method used is descriptive-reflective through the integration of webinar material, theoretical studies, and participant evaluation using Google Forms. The results of the activity showed an increase in participants' understanding of digital skills, soft skills, adaptability, career planning strategies, and the importance of an entrepreneurial mindset. This activity proved to be useful in strengthening Generation Z's readiness to face the digital world of work, thus emphasizing the importance of career education as an effort to empower the younger generation.